Applicant reaction towards selection procedures - Mohd Ferdaus Harun (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
The present study investigates applicants' fairness reactions towards ten selection procedures, examines the difference in reactions between students with and without working experience, and explored the possible interaction effect between selection procedures and working experience on the formulation of reactions. A cross-sectional survey consisting of Steiner and Gilliland's (1996) items was used on 282 undergraduate and postgraduate students. Results of a 2 x 10 mixed ANOVA indicate that there were significant main effects of both selection procedures and working experience on applicants' reactions as was their interaction. Follow-up analyses show that Interview and Work Sample Test were the two most favourable procedures in the present sample while Graphology was rated the least favourable procedure. On the other hand, participants without working experience, unlike, their counterparts evaluated selection procedures more favourably. Applicant reactions were noted higher in the absence of working experience on five selection procedures: Résumé, Biographical Information Blank, Personal References, Personality Test and Graphology. Potential explanations of these findings were discussed in light of the Organizational Justice theory, individual characteristics, and cultural and contextual influence. Implications, strengths, limitations, and recommendations for future research were also discussed.